Antioxidant Stability of Edible Oil Using Rheological Behaviour and in vitro Analysis - RUBALYA VALANTINA*, S.; GAYATHRI!, K. (Asian Journal of Chemistry, 2010)
In food industry, rheological behaviour and thermal degradation are the important parameters required to determine the quality and stability of food system. In this paper, the rheological behaviour and thermal degradation of sunflower oil and palm oil, is investigated. The Newtonian behaviour of the oils are studied from the kinematic viscosity of unused edible oils (sunflower oil, palm oil, groundnut oil, coconut oil, olive oil, sesame oil) using redwood viscometer at temperatures from 30 to 90 ºC. Increase in viscosity of used (heated to frying condition, 210 ºC) edible oils like sunflower oil, palm oil are studied in the same variation of temperature shows the non-Newtonian behavoiur of the oils. This oxidation process can be prevented or retarded by the addition of synthetic or natural antioxidants. The antioxidant activities in oils on heating to smoke point are analyzed using in vitro studies. The free radical scavenging activity of the samples using ABTSH and DPPH is measured and the antioxidant activity of sunflower oil is much effective than palm oil.